2007
DOI: 10.1029/2005jg000107
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil organic carbon induced by tillage and water erosion on a steep cultivated hillslope in the Chinese Loess Plateau from 1898–1954 and 1954–1998

Abstract: (2007), Changes in soil organic carbon induced by tillage and water erosion on a steep cultivated hillslope in the Chinese Loess

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 34 publications
3
44
1
Order By: Relevance
“…Other studies conducted under varied agro-environmental conditions also reported a signifi cant relationship -generally linear -between SOM, 137 Cs and soil erosion/sedimentation (2010) rates (Ritchie et al, 2005;Zhang et al, 2006 Li et al (2007) demonstrated that tillage erosion also moved soil and SOM over cultivated hillslopes, following the same physical mechanisms as water erosion.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies conducted under varied agro-environmental conditions also reported a signifi cant relationship -generally linear -between SOM, 137 Cs and soil erosion/sedimentation (2010) rates (Ritchie et al, 2005;Zhang et al, 2006 Li et al (2007) demonstrated that tillage erosion also moved soil and SOM over cultivated hillslopes, following the same physical mechanisms as water erosion.…”
Section: Discussionmentioning
confidence: 92%
“…Position and terrain attributes in the landscape relative to hillslope curvature or slope segment is also considered an important factor in SC variability (Moore et al, 1993;Pennock et al, 1994;Thompson et al, 1997;Arrouays et al, 1998;Gregorich et al, 1998;Gessler et al, 2000;Chaplot et al, 2001;Polyakov and Lal, 2004;Tsui et al, 2004;Yimer et al, 2006;Yoo et al, 2006;Huang et al, 2007;Li et al, 2007). Hillslope position affects soil moisture content (Beven and Kirkby, 1979;Ticehurst et al, 2007), soil temperature and whether the soil experiences net erosion or deposition.…”
Section: Introductionmentioning
confidence: 98%
“…Ritchie et al, 2007;Li et al, 2007;Zhang et al, 2006;VandenBygaart et al, 2012;Van Oost et al, 2005a;Smith et al, 2005;Quine and Van Oost, 2007). Carbon burial in colluvial soils removes C from the actively cycling C pools in the surface layers to the subsoil, where it continues to decompose, albeit at a slower rate.…”
Section: Z Wang Et Al: the Fate Of Buried Organic Carbon In Colluvimentioning
confidence: 99%